Living with spinal cord injury : a wellness approach - Cristian, Adrian, 1964- (Demos Medical Pub., 2004)
About 40% of all people with spinal cord injuries are now over the age of forty-five, and 25% have had their injury for twenty years or more. We now live at a time when medical advances have made it possible for those with spinal cord injuries to live an essentially normal life span, and to lead full, meaningful, and productive lives. As is true for their friends and colleagues, they work, raise families, and compete in sports. The wear and tear associated with aging and SCI means that these individuals must deal with the fact that the effects of normal aging are superimposed on those of the.